2020
DOI: 10.1021/acs.biomac.0c00123
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of High-Purity Lignins via Catalyst-free Organosolv Pulping from Low-Input Crops

Abstract: A catalyst-free organosolv pulping process was applied to cup plant (Silphium perfoliatum, S), Miscanthus grass (Miscanthus x giganteus, M), and the Paulownia tree (Paulownia tomentosa, P), resulting in high-purity lignins with no signals for cellulose, hemicellulose, or other impurities in two-dimensional heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) spectra. Different biomass particle sizes used for the organosolv pulping (1.6–2.0 mm (1); 0.5–1.0 mm (2); <0.25 mm (3)) influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 68 publications
6
43
0
Order By: Relevance
“…winter [55][56][57][58][59][60]. The results regarding the monolignol ratio are in good accordance with HSQC NMR data reported for lignins isolated from Miscanthus crops [31,52,[61][62][63][64][65] with the exception of the polysaccharide-lignin-linkages not found here in this study. This is most likely due to the mild catalyst-free organosolv pulping method used.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…winter [55][56][57][58][59][60]. The results regarding the monolignol ratio are in good accordance with HSQC NMR data reported for lignins isolated from Miscanthus crops [31,52,[61][62][63][64][65] with the exception of the polysaccharide-lignin-linkages not found here in this study. This is most likely due to the mild catalyst-free organosolv pulping method used.…”
supporting
confidence: 90%
“…The organosolv process as a digestion method has proven itself in every case: it delivers pure lignins, free of sugar residues. The reproducibility of the catalyst-free process has recently been confirmed in another study [31]. If the differences in the lignins are not sufficient as a criterion for the preference for a particular genotype, one can judge based on the harvest yield or other criteria specifically relating to the plant itself, e.g.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…According to Martens [163], S. hermaphrodita also has the potential to be used in the manufacturing of natural fibre products, such as alternative turf, and it could even be used as raw material to produce 3D printing resin. Rumpf et al [164] found that through organosolv pulping, they could achieve a high quality lignin yield of 15.7% from S. perfoliatum that could be used to manufacture biodegradable plastics.…”
Section: Forage and Fibrementioning
confidence: 99%